A Comparison of Tylor's and Marett's Views on the Original Form of Religion - Ghorban Elmi; Suzan Anjomerooz (Comparative Theology)
The present descriptive-analytical study compares the theological approach of Tylor and Marett, two anthropologists of religion. Although both of them introduce human beings as the starting point and origin of the formation of religious experience, Tylor’s approach to defining and explaining religion is rationalistic and Marett’s approach is emotionalistic. Tylor emphasizes belief in the definition of religion and considers the first form of human religion to be animism, while Marett emphasizes the psychological components of feeling and, by stating that religious activities and rituals precede beliefs and opinions are rooted in human emotions, he presents a new theory called "animatism" or the experience of Mana about the form of the first religion. By rejecting the existing Tylorian definition of religion based on belief in spiritual beings, Marett started with his minimal definition of religion which includes the taboo-mana formula, where taboo is the negative aspect of the supernatural and Mana is its positive and positive aspect. Marett interprets religious consciousness as Mana or "sacred matter". Mana is the feeling of the presence of a wonderful and mysterious power or force that forms the essence of primitive religion. Mana is a mixture of fear, wonder, and attraction that creates awe in humans, which indicates a submission that is accompanied by wonder, hope, and even love. In fact, awe is formed in the relationship between man and the supernatural, and the supernatural is nothing but Mana. Keywords: Tylor, Marett, Science of Religion, Animism, Animatism. IntroductionPaying attention to religion, its essence, and its explanation has always been one of the issues of concern to philosophers, theologians, and scientists of religion. In this regard, various theories have been presented by scientists, especially anthropologists of religion, especially in the 19th and 20th centuries. Anthropology of religion is one of the branches of cultural anthropology. It studies man as a being who enters into a relationship with what he considers to be superior to nature, and through this relationship, he begins to create and transform symbols. Anthropologists have focused most of their attention on small and homogeneous societies and have studied the so-called "primitive" religions, which can indicate the origin and initial form of religion. Anthropologists of religion look at religion from two perspectives and deal with these issues: one group considers the origin of religion to be human feelings and emotions, and the other group considers human reason as the cause of human inclination towards religion. Tylor and Marett's views on religion and its origin are rationalistic and emotionalistic, respectively. This study compares the scientific approach of these two influential anthropologists in the history of the study of religion and explains why and how religion appeared in human civilization. Materials and MethodsThe approach of this study is comparative. Comparative research method is a type of scientific study that seeks to compare two or more groups of people or things based on certain characteristics. Therefore, this research describes, analyzes, and explains the similarities and differences between the scientific views of Edward Tylor and Marett, two anthropologists of religion, the former explained religion with a rationalist view, and the latter with an emotionalist view. It especially aims to answer this research question: What was their point of view about the first initial form of religion and why and how religion emerged in human civilization? Research FindingsThe first generation of anthropologists always paid attention to the role of religion as an integral part of a cultural field. The part that gives meaning to tradition, written works, and art. Anthropologists such as Tylor and Marett believed that anthropology can be a full-view mirror of the contemporary society and those who want goodness and truth in the refinement of contemporary civilization can get good help from ethnography. Tylor and Marett consider religion as the most important cultural institution and explain it. In explaining why and how human religion appeared, they consider human beings the starting point and origin of the formation of religious experience; therefore, they state that even if the motivation of religion is from outside - from God and through revelation, or from the world and through awe-inspiring its wonders - still the source of the formation of this experience is man himself and he is the agent. It is a matter of religious experience. But in explaining religion, Tylor considered the root of religion in primitive man's belief in the "soul" and believed that primitive man believed in the existence of a soulmate (soul) in his physical experience in states such as trance and sleep, and the experience of death as the separation of the soul from the body. In its development, this belief leads to the generalization of the concept of soul or ghost to all beings, including objects, animals, plants, and natural phenomena, and to the belief in the existence of spirits of ancestors and the worship of them. Primitive man believed that his fate is in the hands of spirits who are present everywhere and in everything; some of them are good and some are evil, but all of them have the power to change his life. In the continuation of this evolutionary movement, Tylor points to the creation of a kind of harmony between the transcendental and unseen spirits and powers (gods) and finally believes that this is the course of evolution that ultimately leads to monotheism. But Marett, by criticizing Tylor's theory that early religion believed in spirits, put forward the theory of pre-animism and belief in a power called Mana, and he believes that in Mana we have evidence of a pre-animist stage; the stage in which the feeling dominates the thought or in which the thought is still not separated from the feeling. Marett considers the origin of the emotions that rule ritualistic religious behavior to be the presence of an amazing and mysterious power or force from primitive peoples, which he calls Mana. Thus, the origin of religion is an emotion that is a mixture of fear, respect, and amazement and causes awe in humans, which is the most important component of religion and religiosity. Discussion of Results and ConclusionsMarett accepts Tylor's explanation of animism but rejects it as the first form of religion. In his opinion, animism is the next evolution of the motivations that first arose from the emotions resulting from the experience of Mana. The stage where religion and magic are not clearly distinguished from each other and their common element is Mana. He presented a new theory called "animatism", the main ingredient of which is the supernatural, which is a matter of feeling, not reason. According to Marett, it was the idea of ​​Mana that moved the place of religious nature for primitive man from the realm of reason (belief) to the realm of feeling. Mana is the feeling of the presence of a wonderful and mysterious power or force that forms the core of primitive religion. Mana is awe-inspiring and its place in his theology is so bold that it summarizes the whole diverse and heterogeneous combination of special religious feelings in one word "Awe", a term that indicates a submission that is associated with wonder, hope, and even love. In the evaluation of Marett's theory, it should be said that Taylor's claim regarding animism as the first form of religion can be criticized in this regard, just like Marett's claim regarding animism because there is no clear evidence on both claims. Although animatism itself is born of "pure direct religious feeling", compared to animism, it has little intellectual maturity.